Autoimmune pancreatitis: pathogenesis, latest developments and clinical guidance. (May 2014) - Okazaki, Kazuichi; Uchida, Kazushige; Sumimoto, Kimi; Mitsuyama, Toshiyuki; Ikeura, Tsukasa; Takaoka, Makoto
Recently, autoimmune pancreatitis has been classified into two subtypes. Type 1 is related to immunoglobulin G4 and type 2 is related to granulocytic epithelial lesions, but pathogenetic mechanisms in both still remain unclear. Apart from type 2 autoimmune pancreatitis, the pathological features of type 1 autoimmune pancreatitis with increased serum immunoglobulin G4/immunoglobulin E levels, abundant infiltration of immunoglobulin G4+plasmacytes and lymphocytes, fibrosis, and steroid responsiveness are suggestive of abnormal immunity such as allergy or autoimmunity. Although pathophysiological conditions seem to be different in each, both respond well to steroid drugs. After remission, the patients with type 1 autoimmune pancreatitis show high relapse rates (30–50% within 6–12 months), whereas those with type 2 autoimmune pancreatitis seldom relapse. After remission, the steroid maintenance therapy and therapeutic strategy for relapsing patients with type 1 is different among local expertise. In this paper, recent advances in pathogenesis and clinical guidance for therapy are discussed.